MULTI OBJECTIVE MODEL FOR BALANCING U-TYPE ASSEMBLY LINE WITH PERMANENT AND TEMPORARY WORKERS - Gede Agus Widyadana (Institute of Research and Community Outreach - Petra Christian University, 2009)
Assembly line balancing is one of the most important management decisions for reducing production costs. So far, many researches have been done in this area. In this research, we expand the U-type line-balancing using goal programming for multi objective model with two goals, i.e., minimized the number of temporary workers and number of cycle time in each station. Additionally, an example to illustrate the model, as well as some analyses is presented. Different amount of time for temporary worker to accomplish their tasks were generated. For some cases, the U-type assembly line is more efficient than the straight one. However, the goal 1 and goal 2 are conflicted